Streptococcal pharyngitis in children: a meta-analysis of clinical decision rules and their clinical variables. Issue 3 (9th March 2013) - Le Marechal, Flore; Martinot, Alain; Duhamel, Alain; Pruvost, Isabelle; Dubos, François
Abstract : Objective: To identify the best clinical decision rules (CDRs) for diagnosing group A streptococcal (GAS) pharyngitis in children. A combination of symptoms could help clinicians exclude GAS infection in children with pharyngitis. Design: Systematic review and meta-analysis of original articles involving CDRs in children. The Pubmed, OVID, Institute for Scientific and Technical Information and Cochrane databases from 1975 to 2010 were screened for articles that derived or validated a CDR on a paediatric population: 171 references were identified. Setting: Any reference including primary care for children with pharyngitis. Data extraction: The methodological quality of the articles selected was analysed according to published quality standards. A meta-analysis was performed to assess the statistical performance of the CDRs and their variables for the diagnosis of GAS pharyngitis. Primary outcome measure: The main criterion was a false-negative rate in the whole population not any worse than that of a rapid diagnostic test strategy for all patients (high sensitivity and low negative likelihood ratio). Results: 4 derived and 12 validated CDRs for this diagnosis in children. These articles involved 10 523 children (mean age, 7 years; mean prevalence of GAS pharyngitis, 34%). No single variable was sufficient for diagnosis. Among the CDRs, that of Joachim et al had a negative likelihood ratio of 0.3 (95% CI 0.2 to 0.5), resulting in a post-test probability of 13%, which leads to 3.6% false-negative rate among low-risk patients and 10.8% overall, equivalent to rapid diagnostic tests in some studies. Conclusions: The rule of Joachim et al could be useful for clinicians who do not use rapid diagnostic tests and should allow avoiding antibiotic treatment for the 35% of children identified by the rule as not having GAS pharyngitis. Owing to its poor specificity, such CDR should be used to focus rapid diagnostic tests to children with high risk of GAS pharyngitis to reduce the antibiotic consumption.